Mitochondrial DNA Phylogenetics of Black Rhinoceros in Kenya in relation to Southern Africa Population. (22nd August 2017) - Githui, Elijah K.; Thuo, David N.; Amimo, Joshua O.; Njagi, Nyamu M.; Gitari, Maryanne M.
Abstract : Black rhinoceros (Diceros bicornis) are highly endangered due to poaching and other anthropological reasons and their protection to rebound the numbers and genetic improvement are necessary remedial measures defined by Rhino International Union of Conservation for the Nature Red List (IUCN). In Kenya black rhino numbers declined from approximately 20, 000 in the 1970s to fewer than 400 in 1982. Wildlife conservation managers effected strategies to manage/breed the remaining rhinoceros populations in Eastern and Southern Africa within regional sanctuaries. This study analyzes the genetic variability of these remnant rhinoceros using Mitochondrial DNA (mtDNA). Majority of the rhinoceros in both Kenyan and Southern Africa group are monophyletic clusters with insignificant genetic variations while some lineages are underrepresented. The Eastern Africa rhinoceros forms a distinct clade from the Sothern Africa counterpart while Tanzania population has admixtures. Tajima-D test showed that these two populations are under different selection pressure possibly due to different history of adverse anthropologic activities. Similarly, the Southern Africa rhinoceros have low genetic diversity compared to the Eastern African population due to extended periods of game hunting during Africa colonization. This study suggests that managed translocations of individual rhinoceros across the separated fragments can be applied to improve their genetic diversity.